Changes in the self-image among the participants of Neurolinguistic Programming Training. - Wypler, Wojciech (Studia Psychologica: Theoria et praxis, 2004)
The article presents results of a research made on the influence of the Neurolinguistic Programming training on self-image of its participants. The research group consisted of 30 participants of a 14-day stationary "NLP Practitioner" training. The research was based on H.G. Gough and A. B. Heilbrun's Adjective Check List. The test was conducted three times: the first and the last day of the training and three months after the completion date of the training. The test results confirmed the hypothesis that the NLP Training has an influence on participants' self-image. The direction and character of changes in self-image are as follows: increased positive self-evaluation, feeling of better socialisation and higher adaptability, increased demand for more positive and authentic relationships with other people, increased acceptance for participants themselves and for various life circumstances, feeling of internal balance, integrity and self-confidence had also been predicted correctly. For majority of the test scores, any differences that occurred between the results of the first and the second measurement remained significant also in the third test.